Practice-enhancing technology: a review of perceptual training applications in sport - Farrow, D. (Sports Technology, 2013)
This paper outlines practice-enhancing technologies commonly referred to as perceptual training approaches that are designed to improve the decision-making skills of athletes outside of the traditional training setting. Contemporary training approaches of this kind that are currently being applied in the high-performance sports setting will be reviewed from both a practical and empirical perspective. The specific features of the natural task that need to be replicated in a perceptual training session to provide the opportunity for transfer from training to the performance setting are then discussed. Finally, future applications and research directions are discussed in the context of challenges for both researchers and practitioners.